2022
DOI: 10.5812/modernc-123225
|View full text |Cite
|
Sign up to set email alerts
|

Median Arcuate Ligament Syndrome with Common Hepatic and Splenic Arteries Directly Originating from the Abdominal Aorta: A Case Report

Abstract: Introduction: Knowledge of the unpaired abdominal vasculature is important for uncomplicated operations. The absent celiac trunk has previously been reported; however, developmental alterations can result in a variety of branching patterns of the downstream arteries from the abdominal aorta. Case Presentation: A 53-year-old female patient with lymphoma underwent abdominopelvic computed tomography (CT) for staging. She had a history of postprandial off-and-on abdominal pain since her youth. CT scan revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is important to stress that anatomical diversity and the presence of different anatomical variations are more of a rule rather than an exception in living beings, and it is of vital importance that this concept should be adopted, primarily in different surgical fields, as well as in radiology. je pacijentkinja od rane mladosti imala istoriju bolova u stomaku, naročito izraženih postprandijalno [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to stress that anatomical diversity and the presence of different anatomical variations are more of a rule rather than an exception in living beings, and it is of vital importance that this concept should be adopted, primarily in different surgical fields, as well as in radiology. je pacijentkinja od rane mladosti imala istoriju bolova u stomaku, naročito izraženih postprandijalno [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mehrnahad et al described a female patient in whom a CT scan revealed the absence of the celiac trunk, with the common hepatic artery and the splenic artery arising directly from the abdominal aorta. The narrowing and angulation of these blood vessels occurred because they were being compressed by the median arcuate ligament (ligamentum arcuatum mediale), which resulted in the patient having a long history (since early youth) of abdominal pain, which was particularly pronounced postprandially [28].…”
Section: Diskusijamentioning
confidence: 99%